Relationship Of Pragmatic Abilities And Social Interaction With Intensity Of Using Gadgets In Kindergarten Children In Surakarta - Roy Romey Mangunsong; Sudarman Sudarman (Jurnal Keterapian Fisik, 2021)
Background: The occurrence of serious problems in children's mental development, that children will become aggressive, lack of social interaction and deteriorating of communication skills, is affected by the introduction of gadgets too early and the intensity of uncontrolled use of gadgets by parents. Aim of this study is to determine the relationship between pragmatic ability and social interaction with the intensity of using gadgets in kindergarten children in Surakarta. Methods: This research was conducted in the kindergarden TK ABA Thoyibah Surakarta, TK Sri Juwita Hanum Surakarta dan TK Negeri Pembina city of Surakarta in april until august 2020. Sample conduct using total sampling technique. Amount of sample is 115 students of kindergarden. The relationship of the variables studied, both pragmatic ability and social interaction with the intensity of using gadgets, is an Odds Ratio (OR), which is exponential from b, the statistical significance of the Odds Ratio is tested with mannova. Results: The results of the analysis of the pragmatic ability variable showed that Exp B: 2,916, p: 0,420. The results of the social interaction variable analysis showed that Exp B: 2,977, p: 0.011. Conclusion: Pragmatic ability and social intensity are jointly related to the intensity of using gadgest in kindergarten students in Surakarta, with the results of the analysis of the variable pragmatic ability Exp B: 2,916, p: 0,420 and the results of the analysis of social interaction variables Exp B: 2,977, p: 0.011.